PENGARUH KONFLIK PERAN, KETIDAKJELASAN PERAN, KELEBIHAN PERAN, GAYA KEPEMIMPINAN, STRUKTUR AUDIT, DAN PEMAHAMAN GOOD GOVERNANCE TERHADAP KINERJA AUDITOR (Studi Empiris Pada Kantor Akuntan Publik Di Provinsi Jawa Tengah Dan DIY) - Widia Sari, 13.05.52.0185; Kartika, Andi (Students' Journal of Accounting and Banking, 2017)
Today the proliferation of Foreign Public Accounting Firm (KAPA) in Indonesia led to the Public Accounting Firm (KAP) local needs by increasing the quality of services rendered in order not to lose competitiveness with the Office of Foreign Public Accountant (KAPA). In addition to the competition between the Public Accounting Firm (KAP) the need to improve the quality of audit services is also reflected in the amount of active public accountant in Indonesia. In 2011, the Indonesian Institute of Accountants (IAI) said Indonesia still lack staff accountant. The number of accountants in Indonesia only 800 people, and only 700 active members.Half of the amount of active accountant who has over 50 years old.The population in this research is the auditors who work at public accountant in the province of Central Java and Yogyakarta. Sampling is performed using the method of purposive sampling. Sample criteria was an auditor who works on the KAP with the minimal level of Education Bachelor degree majoring in accounting with experience working at least a year.Research getting data from the questionnaire which is distributed directly to the auditor. Researchers spread a questionnaire to the KAP of a number of respondents are willing to be 120 questionnaires on KAP in Central Java province and Yogyakarta, but only 81 questionnaires that were returned, and there are 4 questionnaires that do not meet the criteria so that researchers use 77 questionnaire used as the sample for this study.The research of using multiple linear regression analysis. The results showed that a conflict of roles and leadership style effect is not significantly to the performance of the auditor. Whereas, the obscurity of the role, role of excess, the structure of the audit and the understanding of good governance have an effect on the performance of the auditor.Keywords: Role Conflict, Role Ambiguity Regarding The Advantages of Roles, Leadership Style, The Structure of The Audit, The Understanding of Good Governance, and The Performance of The Auditor